2021
DOI: 10.1101/2021.06.28.450160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Herpes simplex virus 1 inhibits phosphorylation of RNA polymerase II CTD serine-7

Abstract: Transcriptional activity of RNA polymerase II (Pol II) is orchestrated by post-translational modifications of the C-terminal domain (CTD) of the largest Pol II subunit, RPB1. Herpes Simplex Virus type 1 (HSV-1) usurps the cellular transcriptional machinery during lytic infection to efficiently express viral mRNA and shut down host gene expression. The viral immediate-early protein ICP22 interferes with serine 2 phosphorylation (pS2) of the Pol II CTD by targeting CDK9. The functional implications of this are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 77 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Recently, it was found that phospho-Ser7 (pS7) is down-regulated in addition to pS2 while the other major CTD modifications are preserved. Both ICP22 and ICP27 seemed to contribute to this loss in fibroblasts [50]. This may occur by the same means as the reduction of pS2 in infection, though pS7 loss was not observed with transient expression of ICP22 in HeLa cells [51].…”
Section: Ctd Phosphorylationmentioning
confidence: 89%
See 3 more Smart Citations
“…Recently, it was found that phospho-Ser7 (pS7) is down-regulated in addition to pS2 while the other major CTD modifications are preserved. Both ICP22 and ICP27 seemed to contribute to this loss in fibroblasts [50]. This may occur by the same means as the reduction of pS2 in infection, though pS7 loss was not observed with transient expression of ICP22 in HeLa cells [51].…”
Section: Ctd Phosphorylationmentioning
confidence: 89%
“…Interestingly, these studies found prevention of pS2 loss with proteasome inhibitors. While the majority of pS2/7 could be residing on a small proportion of hyperphosphorylated IIo in the cell, phospho-CTD reductions occur before a comparable drop in total RPB1 protein levels in multiple cell types indicating that remodeling is regulated beyond bulk turnover [47,50]. In contrast to HeLa cells [72], total RPB1 protein levels were stable through the peak of viral transcription in primary fibroblasts, while an almost complete loss was observed by 24 hpi.…”
Section: Ctd Phosphorylationmentioning
confidence: 95%
See 2 more Smart Citations